Genome-Wide Screen for Haploinsufficient Cell Size Genes in the Opportunistic Yeast Candida albicans. Issue 2 (1st February 2017) - Chaillot, Julien; Cook, Michael A; Corbeil, Jacques; Sellam, Adnane
Abstract: One of the most critical but still poorly understood aspects of eukaryotic cell proliferation is the basis for commitment to cell division in late G1 phase, called Start in yeast and the Restriction Point in metazoans. In all species, a critical cell size threshold coordinates cell growth with cell division and thereby establishes a homeostatic cell size. While a comprehensive survey of cell size genetic determinism has been performed in the saprophytic yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe, very little is known in pathogenic fungi. As a number of critical Start regulators are haploinsufficient for cell size, we applied a quantitative analysis of the size phenome, using elutriation-barcode sequencing methodology, to 5639 barcoded heterozygous deletion strains of the opportunistic yeast Candida albicans . Our screen identified conserved known regulators and biological processes required to maintain size homeostasis in the opportunistic yeast C. albicans . We also identified novel C. albicans -specific size genes and provided a conceptual framework for future mechanistic studies. Interestingly, some of the size genes identified were required for fungal pathogenicity suggesting that cell size homeostasis may be elemental to C. albicans fitness or virulence inside the host.